Determinação multiclasse de resíduos de agrotóxicos e medicamentos veterinários em carnes por LC-MS/MS - Friggi, Caroline do Amaral (2012)
The agribusiness has been incorporating new technologies in the production of meat, including good management of farms, health, balanced diet, breeding and integrated production. Allied to this, there is a growing concern with issues related to residues and contaminants in animals intended for food production. In the study, were compared four extraction methods based on the method QuEChERS for the determination of 79 pesticides and 15 veterinary drugs analyzed by Liquid Chromatography coupled to tandem Mass Spectrometry in samples of meat and pork liver, chicken and fish. The parameters evaluated were: linear range (6 concentration levels and 6 injections each), limit of detection (LOD), limit of quantification (LOQ), decision limit (CCα), capability of detection (CCβ) and matrix effect, as well as precision and accuracy, in terms of recovery. For this, we performed the fortification of matrices previously homogenized with solutions containing compounds at 3 levels of fortification (20, 50 and 100 μg kg-1), 6 replicates for each level, were performade. The modified QuEChERS extraction method consists in the extraction of 10 g of the matrix with 10 mL of acetonitrile containing 1% (v/v) of acetic acid and shaking vigorously by hand for 1 min. After, 4 g of anhydrous magnesium sulfate and 1.7 g anhydrous sodium acetate were added and the agitation repeated. After the extract was centrifugated for 8 min (3500 rpm) and 2 mL of the extract was transferred to another tube containing 300 mg of anhydrous magnesium sulfate and 50 mg of sorbent PSA, repeating the agitation and centrifugation. The extract was diluted (1:1 v/v) in the mobile phase and then analyzed by LC-MS/MS. Analytical curves prepared in solvent and in extracts of matrices evaluated showed adequate linearity between 5 and 200 μg kg-1, with coefficients of determination greater than 0.99. The method showed satisfactory recovery values between 70 and 120% (RSD ≤ 20%) to about 95% of compounds in all matrices, except for liver showed satisfactory values to about 80% of the compound at levels of 20, 50 and 100 μg kg-1. The LOQ of method was 10 μg kg-1. CCα values were between 1.1 and 102.9 μg kg-1 and CCβ values were in the range 1.9 to 105.9 μg kg-1. The results of this study showed that the modified method QuEChERS is fast, simple and efficient and can be applied to the determination of pesticides and veterinary drugs in samples of meat and liver pork, chicken and fish fillet for routine analysis. Furthermore, the use of LC-MS/MS was efficent, allowing the determination and confirmation of a large number of compounds simultaneously at residues livels.